ANALISIS TERHADAP TANDA BUKTI HAK ATAS TANAH BERDASARKAN UUPA DAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TERKAIT PENGGUNAAN GIRIK NOMOR 87 PERSIL 157 KELURAHAN CENGKARENG BARAT (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 2459K/PDT/2014) - Stella .; Hasni . (Fakultas Hukum Universitas Tarumanagara, 2018)
Since of Agrarian Law in Indonesia, western right land and communal right land have been converted into land right according to Agrarian Law so the state is obliged to provide legal assurance through land registration, with the end product is certificate as a proof of title. Proof is an important part of law society as it is the legal standing of land ownership. A strong proof of title is defined in the Agrarian Law and Government Regulation as the implementing regulation, however Indonesian society especially low-economy society still the old proof of title. The main issue is how Customary Title Status relates to the proof of land right in the national land law and judge of Supreme Court made in consideration in resolving civil dispute number 2459K/Pdt/2014 on use of customary land title no.87 land parcel 157 West Cengkareng urban village. Based on the research outcome, that the existence of customary land title is still recognized to this date only as one of the requirements in the land registration process to prove the old title and conversion of communal land so that decision of Supreme Court is correctly made that customary land title is not a form of land ownership since there is no agency except National Land Agency can issue proof of title that is certificate. As of the result of this, certificate is a strong proof of land title. So should, there is an importance common understanding of customary land title from fiscal cadaster rather than legal cadaster.